The Basis for the Judge's Consideration of the Brebes Religious Court on Granting Permission for Marriage Dispensation in Decision Number 179/Pdt. P/2023/Pa. BBS After Jo Kawin Anak Program - Rojak, Encep Abdul; Yulia, Marsella; Hayatudin, Amrullah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
The marriage dispensation is intended for someone who wants to get married but is hindered because the minimum age limit for marriage is 19 (nineteen) years. One of the decisions related to this marriage dispensation is in case Number 179/Pdt.P/2023/PA.Bbs, which in its application requested the Panel of Judges as state officials to grant the request for marriage dispensation to their daughter, who is still aged 18 (eighteen) years. This research is field research, using qualitative analysis techniques with an inductive mindset. The results of this study are the factors that cause the application for marriage dispensation, namely because the parents are concerned for their children, who are already very close to their future husbands, so if they do not get married immediately, it is feared that they will fall into immoral acts. As for the consideration of the Panel of Judges in granting the request for marriage dispensation in Case Number 179/Pdt.P/2023/PA.Bbs after the Jo Kawin Boy programme in Central Java, namely considering the daughter of the petitioner who has been engaged since 1 (one) a year ago and is known to have had a love affair for 3 (three) years with her future husband, it is feared that if she does not get married soon, it will cause harm.Dispensasi pernikahan ditujukan bagi seseorang yang ingin melangsungkan pernikahan akan tetapi terhalang karena batas usia minimal pernikahan yaitu 19 (Sembilan belas) Tahun. Salah satu Putusan terkait dengan dispensasi pernikahan ini yaitu pada perkara Nomor 179/Pdt.P/2023/PA.Bbs, yang dalam permohonannya tersebut memohon Majelis Hakim selaku pejabat Negara untuk mengabulkan permohonan dispensasi pernikahan pada anak perempuannya yang masih berusia 18 (delapan belas) tahun. Penelitian ini merupakan penelitian lapangan (Field Research), menggunakan teknik analisis kualitatif dengan pola pikir induktif. Hasil dari penelitian ini yaitu faktor yang manjadi penyebab permohonan dispensasi pernikahan yaitu karena faktor kekhawatiran orang tua terhadap anaknya yang sudah berhubungan sangat dekat dengan calon suaminya sehingga jika tidak segera melangsungkan pernikahan dikhawatirkan akan terjerumus kedalam perbuatan maksiat. Adapun yang menjadi pertimbangan Majelis Hakim dalam mengabulkan permohonan dispensasi pernikahan pada Perkara Nomor 179/Pdt.P/2023/PA.Bbs, setelah adanya program Jo Kawin Bocah di Jawa Tengah yaitu mempertimbangkan anak Perempuan dari Pemohon yang sudah bertunangan sejak 1 (satu) Tahun yang lalu dan diketahui sudah memiliki hubungan cinta selama 3 (tiga) Tahun dengan calon suaminya tersebut, sehingga dikhawatirkan jika tidak segera menikah akan menimbulkan banyak kemudharatan.